High‐salt intake reduces renal tissue levels of inflammatory cytokines in mice. Issue 24 (20th December 2020) - Singh, Purnima; Stephenson, Roxan; Castillo, Alexander; Majid, Dewan S. A.
Abstract: High salt (HS) intake is usually considered as an aggravating factor to induce inflammatory renal injury. However, the changes in the renal levels of inflammatory cytokines during HS intake is not yet clearly defined. We hypothesize that HS increases renal levels of tumor necrosis factor‐alpha (TNF‐α) and interleukin‐6 (IL‐6) but decreases interleukin‐10 (IL‐10; anti‐inflammatory cytokine) and these responses exacerbate in NO deficient conditions. Both wild‐type (WT) and endothelial NO synthase knockout (eNOSKO) mice (~8 weeks old, n  = 6 in each group) were given normal‐salt (NS; 0.3% NaCl) and HS (4% NaCl) containing diets for 2 weeks. Systolic blood pressure (SBP) was determined by tail‐cuff plethysmography and urine collections were made using metabolic cages. Basal SBP was higher in eNOSKO than WT mice (131 ± 7 vs 117 ± 3 mmHg; p  < .05). HS intake for 2 weeks increased SBP in eNOSKO (161 ± 5 mmHg) but not in WT mice. In NS groups, the cytokine levels in renal tissues (measured using ELISA kits and expressed in pg/mg protein) were significantly higher in eNOSKO than WT mice (TNF‐α, 624 ± 67 vs. 325 ± 73; IL‐6, 619 ± 106 vs. 166 ± 61; IL‐10, 6, 087 ± 567 vs. 3, 929 ± 378). Interestingly, these cytokine levels in HS groups were significantly less both in WT (TNF‐α, 114 ± 17; IL‐6, 81 ± 14; IL‐10, 865 ± 130) and eNOSKO (TNF‐α, 115 ± 18; IL‐6, 56 ± 7; IL‐10, 882 ± 141) mice. These findings indicate that HS induces downregulation of cytokines in the kidney. Such HS‐induced reduction in cytokines, particularly TNF‐α (a natriuretic agent), would facilitate more salt‐retention, and thus, leading to salt‐sensitive hypertension in NO deficient conditions. Abstract : This study examined the renal levels of inflammatory cytokines during high salt (HS; 4% NaCl in diet) intake for 2 weeks in mice. The findings indicate that HS induces a downregulation of cytokines in the kidney. Such HS induced reduction in cytokines, particularly TNF‐α (a natriuretic agent), would facilitate more salt‐retention and thus, leading to salt‐sensitive hypertension in NO deficient conditions.